(3cJGH GdSfIs - (3YHO Gddg Hf CMeO , YHO Gddg Hf CMeO Hf eMeO Hf MfHd, CHh YHO GdQMef,J (B290 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bGd GdEeGe CHh YHO GdQMef YHO Gddg Hf GdEeGe CHj YHO Gddg CMeO HfeMeO Hf MfHd QVi Gddg YfgeG hbO SFd Ydi eG bdJg GdYdeGA ai GdLgejI GdVdGd hCcaGQge hGdUdGg Ndage s
(3BNQgG (B:s
(3SeYJ CHj jbhd ef bGd GdbQBf eNdhb agh YfOfG cGaQ dCf GdbQBf ef Yde Gddg hajg CSeGA Gddg GdfgGji bGd SeYJ YGFTI bGdJ (B( (3Ef GdcGaQ jSdW Ydjg ai GdbHQ TLGY CbQY jCcdg ef QCSg MJi jfJgi Zdi bOeg Ke jcSi dMeGk ajCcdg ef bHd bOeg MJi jfJgis
(3HgG fXGe GdJYbjHIs
(3LRAGf ai eLdOs
(3ai GdQO Ydi GdLgejIs
(3gPg gi GdfSNI GdhMjOI GdcGedI Ydi eG ai HQhcdeGf s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
Keywords: (3GdMOjK h GdeUWdMs